Concept mapping to promote clinical reasoning in multimorbidity - Fonseca, Marta (2024)
Funding Information: This study did not apply for any funding. Article processing charges were funded by Funda\u00E7\u00E3o Ci\u00EAncia e Tecnologia, IP national support through CHRC (UIDP/04923/2020). Publisher Copyright: © The Author(s) 2024.